Hotaka [a novel] - Heffernan, John (Allen & Unwin, 2017)
When the tsunami strikes the Japanese seaside town of Omori-wan, the effects are utterly devastating. Three years later, much of what happened on that day is still a mystery. As Hotaka sets about convincing local performers to appear at the town's upcoming Memorial Concert, he finds himself increasingly haunted by memories of best friend, Takeshi, who perished without trace in the tsunami. Then his friend Sakura becomes involved in an anti-seawall movement, and all too quickly the protest gets serious. As the town and its people struggle to rebuild their lives, can Hotaka piece together what happened that day - and let go of the past?
Keywords: Tohoku Earthquake and Tsunami (Japan : 2011); Tohoku Earthquake and Tsunami, Japan, 2011 / Juvenile fiction; Friendship / Juvenile fiction; Grief / Juvenile fiction; Australian fiction; Young adult fiction; Children's, Teenage & educational; Friendship; Grief; Japan / Tōhoku Region; Tohoku Earthquake and Tsunami, Japan, 2011 / Fiction; Tsunamis / Japan / Fiction; Sea-walls / Fiction; Grief / Fiction; 2011; Fiction; Juvenile works; Children's fiction; Jugendbuch